Factors influencing blockchain adoption in the tourism industry: An empirical study - González-Mendes, S.; González-Sánchez, R.; Costa, C. J.; García-Muiña, F. E. (Technology Analysis and Strategic Management, 2026)
The adoption of blockchain technology is gaining trends, leading to the need for investigations into the reasons that persuade the intention to adopt it by companies. However, empirical studies in the tourism industry are still scarce. This investigation aims to design a new adoption model that combines Human-Organisation-Technology-Fit (HOT-fit), Technology-Organisation-Environment (TOE) and sustainability dimensions. The model is validated using new empirical evidence in a relatively understudied geographic context, with a sample of 210 Portuguese tourism companies. The information was examined utilising Partial Least Squares Structural Equation Modelling (PLS-SEM). The outcomes indicate that reasons such as sustainability and competition intensity significantly impact the objective to adopt blockchain. The work provides practical implications for businesses, governments and society. Additionally, this paper offers a pioneering study of blockchain adoption by tourism companies in Portugal, which may help future researchers extend their study of this field to other sectors and regions.